MODEL COOPERATIVE SCRIPT UNTUK MENINGKATKAN KEAKTIFAN SISWA DI SEKOLAH DASAR - Nurlinda Safitri; Fitri Anjaswuri; Derista Lidya Carolina (Universitas Pakuan, 2020)
SCRIPT COOPERATIVE MODEL TO IMPROVE STUDENT ACTIVITY IN PRIMARY SCHOOL This research was conducted using Classroom Action Research. The implementation of research activities is carried out in 2 stages or 2 cycles. The purpose of this study was to increase the activeness of students in elementary schools using a cooperative script model on the sub-theme of Cultural Diversity in the Nation which was applied to grade IV C SDN Gunung Gede, North Bogor District, Bogor City which consisted of 30 students. Research activities were carried out in the Odd Semester of the 2020/2021 Academic Year. In cycle 1, the learning media used was a popup book. While the learning media used in cycle 2 were hand puppets. The results of this study indicate that the cooperative script model is an effective model to be used in this study. There was a significant change in the average value of activeness between cycle 1 and cycle 2. Based on the results of the learning activities carried out by the researcher, data was obtained that in cycle 1 the average value of student activity was 71 while in cycle 2 it again increased to 92. In addition , in cycle 1 classical completeness was 43% and in cycle 2 classical completeness was 100% where all students scored above the KKM. The difference in classical completeness is 57%. Based on the results of the research that has been carried out, it can be concluded that the cooperative script model is an effective model that can be applied in this study. In addition, the use of cooperative script learning models can increase student activeness from the assessment cycle 1 to cycle 2